Analisis Koneksi Matematika dalam Penyelesaian Soal Cerita Materi Himpunan pada Siswa Kelas VII SMP Negeri 2 Baki Sukoharjo - Lestari, Dina, Masduki, S.Si., M.Si (2017)
The purpose of this research are: analyze the connection of mathematics students in recognizing concepts, in relating the concepts, and in applying the concepts set to complete a story problems on the set material. This research is descriptive a kind of qualitative one which subjects is 6 students of class VII E SMP Negeri 2 Baki Sukoharjo. Data collection method used in this research are observation, test, interview, and documentation. Mechanical analysis of data through data reduction, data presentation, and pulling of conclusions. The validity of the data use credibility test. The results of this research indicate to the connection of mathematics students to solving the story problems is still low. Based on the results obtained: 1) Capability connection mathematics students in recognizing the concepts to students with a value of more than minimum learning masteri standart almost different with students who scored less then minimum learning masteri standart, 2) Capability connection mathematics students to understand the interrelatedness of concept to students with a value of more than minimum learning masteri standart be same as students who scored less then minimum learning masteri standart , 3) Capability connection mathematics students in applying the concepts to students with a value of more than minimum learning masteri standart almost same as students who scored less then minimum learning masteri standart.